2019
DOI: 10.1055/s-0040-1709814
|View full text |Cite
|
Sign up to set email alerts
|

Single-Balloon Enteroscopy—Guided ERCP in Surgically Altered Anatomy Is Safe and Highly Effective: Results from a Prospective Study

Abstract: Objectives Single-balloon enteroscopy (SBE)—assisted endoscopic retrograde cholangiopancreatography (ERCP) has been shown to be cost effective and less technically demanding than other modes of device-assisted enteroscopy. We aimed to evaluate the safety and efficacy of SBE-ERCP in surgically altered anatomy. Methods This was a prospective cohort study in a high-volume tertiary care gastroenterology center. Patients with surgically altered anatomy requiring pancreaticobiliary interventions, who failed ERCP wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the SBE-ERCP group, stents were mostly plastic and of smaller caliber, and the obstructions were often incomplete, potentially leading to cholangitis. [15][16][17][18] A meta-analysis comparing endoscopic drainage with PTBD showed that although PTBD had a higher success rate, it was associated with more stent migrations, repeated interventions, and recurrent cholangitis. Another randomized controlled study comparing EUS-guided biliary drainage and PTBD in malignant biliary obstruction with failed ERCP revealed fewer complications, reinterventions, and adverse events in the EUS group compared to PTBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the SBE-ERCP group, stents were mostly plastic and of smaller caliber, and the obstructions were often incomplete, potentially leading to cholangitis. [15][16][17][18] A meta-analysis comparing endoscopic drainage with PTBD showed that although PTBD had a higher success rate, it was associated with more stent migrations, repeated interventions, and recurrent cholangitis. Another randomized controlled study comparing EUS-guided biliary drainage and PTBD in malignant biliary obstruction with failed ERCP revealed fewer complications, reinterventions, and adverse events in the EUS group compared to PTBD.…”
Section: Discussionmentioning
confidence: 99%
“…In the SBE-ERCP group, stents were mostly plastic and of smaller caliber, and the obstructions were often incomplete, potentially leading to cholangitis. 15 16 17 18…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic success was achieved in 86.95 and 94.1% of patients with Roux-en-Y and Billroth II anatomy with an immediate complication rate of 7.5% in the form of perforation. 52 In another study by Garcés-Durán, feasibility and safety of SBE-ERCP in post-PD anatomy were assessed; 34 patients underwent 106 SBE-ERCP, 76 procedures performed for biliary indication had a 90% technical success and 88% clinical success rate, whereas among 30 procedures performed for pancreatic intervention technical success rate was 80% and the clinical success rate was 65%. 53 While either side-view or forward-viewing scopes can be used, passage of a side-view scope into the afferent limb is often tricky.…”
Section: Endoscopic Retrograde Cholangiopancreatography In Postpancre...mentioning
confidence: 99%